URINARY EXTRACELLULAR VESICLE PROTEINS AS SIGNATURES FOR CRIBRIFORM AND INTRADUCTAL PROSTATE CARCINOMA - Bernardino, Rui; Sayyid, Rashid; Fleshner, Neil; Carvalho, Ana Sofia; Matthiesen, Rune; Leão, Ricardo; Pereira, Hermínia; Pinheiro, Luis Campos; Beck, Hans Christian; Henrique, Rui (Urologic oncology, 2024)
Current imaging and diagnostic tools perform poorly for the reliable prediction of presence of intraductal carcinoma and cribriform pattern at prostate biopsy.;The presence of those patterns has been consistently demonstrated to be associated with adverse prostate cancer outcomes, including increased risks of biochemical recurrence, metastasis, and cancer-specific mortality. Biomarkers to better detect these histological patterns are needed.;Prostate cancer (PCa) proteome changes occur during initiation and progression of the disease, and a quantitative systemic overview of these changes may lead to clinically relevant findings. Proteins, the primary effectors of most cellular reactions, are drug targets and serve as potential biomarkers. PCa tissue proteome has been previously characterized but screening of tissue samples;constitutes an;invasive procedure.;We focused this study on liquid biopsies such as urine samples.;The main objective of this study is to identify a biomarker for PCa patients with cribriform pattern and intraductal PCa (IDC). Urinary small extracellular vesicle (EV) proteome profiles of 100 subjects were analyzed using liquid chromatography coupled to high-resolution mass spectrometry (LC-MS/MS).;Small EVs isolated from urine of healthy donors (HD, N = 24), patients without cribriform and IDC histological prostate patterns submitted to radical prostatectomy (non-IDC/non-Crib, N = 21), and patients with cribriform and/or IDC histological prostate patterns (IDC/Crib, N = 55) were analyzed by bottom-up proteomics. We identified 171 proteins that were differentially expressed between IDC/Crib and non-IDC/non-Crib after correction for multiple testing. Functional enrichment analysis based on cancer hallmark proteins disclosed a clear pattern of androgen response down-regulation in urinary EVs from IDC/Crib compared to non-IDC/non-Crib. Interestingly, proteome differences between IDC and cribriform were more subtle suggesting high heterogeneity. Overall the urinary EV proteome appears to reflect the prostate pathology. TMBIM1, also known as Bax inhibitor 1 (BI-1), was among those most upregulated in Crib and IDC compared to cancer without IDC/Crib (Figure 5B-D). Bax inhibitor 1 (BI-1), plays a crucial role in regulating apoptosis and calcium homeostasis by inhibiting the activity of the pro-apoptotic protein Bax and protecting cells from apoptosis induced by various stimuli. Bax inhibitor-1 specific down-regulation by RNA interference leads to cell death in human PCa cells. TMBIM1 has also been previously identified as up-regulated in urinary EVs in patients with high-grade prostate cancer (poor prognosis).;Based on our analysis, we conclude that the proteome of small urinary EVs holds diagnostic potential and appears to reflect the proteome of prostate tissue. Urinary EV proteome highlighted proteins with a role in androgen response, epithelial mesenchymal transition, fatty acid metabolism and reactive oxygen species as prognostic factors for prostate cancer.